2009 IEEE International Conference on Acoustics, Speech and Signal Processing 2009
DOI: 10.1109/icassp.2009.4960346
|View full text |Cite
|
Sign up to set email alerts
|

An approximate L0 norm minimization algorithm for compressed sensing

Abstract: 0 norm based signal recovery is attractive in compressed sensing as it can facilitate exact recovery of sparse signal with very high probability. Unfortunately, direct 0 norm minimization problem is NP-hard. This paper describes an approximate 0 norm algorithm for sparse representation which preserves most of the advantages of 0 norm. The algorithm shows attractive convergence properties, and provides remarkable performance improvement in noisy environment compared to other popular algorithms. The sparse repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 9 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…0 sparsity based approaches have been widely used in many vision and graphic tasks and acquired superior performance. Hyder and Mahata [23] proposed an iteratively approximate 0 -norm based on fixed point to reconstruct sparse signal and achieved an obvious improvement in noisy environment. In [10,24], Xu et al developed 0 gradient minimization to control the nonzero gradients among neighborhoods, which indicated that the prominent image structures needed to be preserved in image smoothing.…”
Section: Related Workmentioning
confidence: 99%
“…0 sparsity based approaches have been widely used in many vision and graphic tasks and acquired superior performance. Hyder and Mahata [23] proposed an iteratively approximate 0 -norm based on fixed point to reconstruct sparse signal and achieved an obvious improvement in noisy environment. In [10,24], Xu et al developed 0 gradient minimization to control the nonzero gradients among neighborhoods, which indicated that the prominent image structures needed to be preserved in image smoothing.…”
Section: Related Workmentioning
confidence: 99%
“…However this algorithm is known to be NP-hard [12] for the same reason as RIP checking is NP-hard. This would seem to be a serious road-block.…”
Section: Recovery Algorithmsmentioning
confidence: 99%
“…The ℓ 2 − ℓ 0 approach has been shown in the literature to be advantageous in many applications, for instance sparse component analysis [44], compressive sensing [32], matrix completion [41], robust regression [42], segmentation [52], and image recovery [20,49]. This paper mainly addresses the latter problem, where ℓ 2 − ℓ 0 is recognized for its ability to preserve edges between homogeneous regions [45].…”
Section: Introductionmentioning
confidence: 99%